2013
DOI: 10.3171/2012.11.jns12362
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effect of YM872 and AG1296 combination treatment on human glioblastoma xenograft models

Abstract: The strongly enhanced antitumor effect of this combination therapy in vivo rather than in vitro may be attributable to disruption of the aberrant vascular niche. This combination therapy might provide substantial benefits to patients with glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…The present study examined the effect of tyrphostin AG 1296 on glioblastoma cell growth and migration in vitro and in vivo . In accordance with previous studies ( 23 , 24 ), tyrphostin AG 1296 exhibited marked efficacy in the inhibition of glioblastoma cell growth and migration in vitro . Furthermore, it was demonstrated that tyrphostin AG 1296 induced cell apoptosis in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study examined the effect of tyrphostin AG 1296 on glioblastoma cell growth and migration in vitro and in vivo . In accordance with previous studies ( 23 , 24 ), tyrphostin AG 1296 exhibited marked efficacy in the inhibition of glioblastoma cell growth and migration in vitro . Furthermore, it was demonstrated that tyrphostin AG 1296 induced cell apoptosis in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that tyrphostin AG 1296, an inhibitor of PDGFR, reduces glioblastoma cell proliferation ( 24 ). In order to confirm whether tyrphostin AG 1296 affects glioblastoma cell growth, a cell viability assay was performed in U87MG cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting ionotropic glutamate receptors to reduce proliferation and invasion of GB, promising preclinical data exist inter-alia for AMPAR- and NMDAR-inhibitors including memantine [ 3 , 6 , 8 , 11 , 15 , 16 , 20 , 46 ]. As radiotherapy plays a central role in GB treatment, testing for radiosensitizing potential of glutamate receptor targeted therapy to enhance irradiation’s effectiveness appears sensible especially from a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In Fibroblasten und kolorektalen Karzinomzelllinien konnte außerdem gezeigt werden, dass SRC einen Komplex mit EGFR bilden kann, in dessen Folge der EGFR und die nachfolgenden Signalwege auch ohne Ligandenbindung aktiviert werden (Maa et al, 1995, Stover et al, 1995. einen Arrest der Zellen in der G1-Phase des Zellzyklus bewirkt (Vigneron et al, 2005, Mamidipudi et al, 2007, Hikita et al, 2010 Ergebnisse der PDGFR-β-Inhibition in Prostatakarzinom-, Glioblastom-, Bronchialkarzinomund Kolonkarzinomzellen zeigen jedoch (Roberts et al, 2005, Yokoi et al, 2005, Park et al, 2011, Watanabe et al, 2013…”
Section: Mittels Immunzytochemischemunclassified